The universal applicability of the theory of neutralization: German youth coming to terms with the Holocaust - Hazani, Moshe (Crime, law and social change, 1991)
The purpose of this article is twofold. Empirically, it dwells on the little studied instance of people who never transgresses any legal or moral code, yet nonetheless experience tension resulting from inner norms/behavior conflict and resort to neutralization techniques to smooth this conflict. The subjects studied were German youths; while they had all been born after World War II, their sense of German historical continuity made them feel responsible for the crimes committed under the Nazi regime. It was found that in order to overcome the conflict between the humanist values they professed and the memory of the Holocaust, they employed four of the neutralization techniques habitually used by delinquent boys, as described by Sykes and Matza. Theoretically, the article contends than Sykes and Matza's theory of neutralization is a specific instance of the socio-psychological cognitive consistency theory, and shows that the techniques enumerated by Sykes and Matza are embraced by the models constructed by students of that theory. At the same time, however, the article shows that Sykes and Matza's approach, which can be applied to non-delinquents and to situations which do not involve guilt, elucidates how people restore equilibrium without attitude change, a topic little explored by social psychologists. The article also discusses two universal modes of resolution of dilemmas: abstraction and relativization.